PENINGKATAN KUALITAS PROSES BELAJAR DAN HASIL BELAJAR SEJARAH MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION PADA SISWA KELAS VIIIH , SEMESTER 2 SMP PGRI 5 DENPASAR TAHUN PELAJARAN 2009/2010 - Aryanta, I Made Swarika; Subali, Yohanes (Jurnal Santiaji Pendidikan (JSP), 2011)
This Classroom Action Research was carried out at SMP PGRI 5 Denpasar class VIII H, second semester in academic year 2009/2010. The purposes of this research are: 1). to know the process of learning in the classroom, 2). to improve the quality of the process of learning History, and 3). to improve the students’ learning achievement in History through cooperative learning method type G.I. (Group Investigation). The learning activities in the classroom were held in two cycles, they are : cycle I and cycle II. Every cycle consists of four stages: planning, action, observation, and reflection. The techniques used for collecting the data are as follows : (1) distributing observation sheet, (2) taking notes on some documents, (3) conducting interviews to the subjects and (4) giving formative tests. For the data analysis in this study, descriptive qualitative analysis and simple quantitative analysis are used.. The result of this research showed that the application of learning process of History using cooperative leaning method type G.I. could be well applied to the students of class VIII H second semester in SMP PGRI 5 Denpasar ; Group Investigation method could sharpen the students’ ability academically as well as socially; the application of cooperative learning model G.I. could increase the quality of History learning process based on the result of observation from the students’ activities during the learning process which showed better result in every session from cycle I to cycle II. Futhermore, the students showed their enthusiasm and high motivation in doing their tasks, presentations and discussions. Besides, their attention, concentration, interaction, creativity, cooperation in group and their work in the form of worksheet or report showed better increase; the application of cooperative learning type G.I. could increase the students’ achievement in learning History, with the average absorption capacity around 70,9 %. And the learning mastery level is around 69 % in the cycle I and it increased in cycle II becoming 73,1 % with absorption capacity 73,1% and the learning mastery level is 100%. Thus, the cooperative learning model G.I. could be applied as one of the alternatives in learning History at school because it could increase the students’ enthusiasm and also the students’ learning achievement.